Let's solve the equation step-by-step:
The equation given is:
\[ -6(x - 2) + 3x = -3(x + 3) + 21 \]
First, we'll distribute the terms on both sides:
For the left side:
\[ -6(x - 2) = -6x + 12 \]
So the left side becomes:
\[ -6x + 12 + 3x = -3x + 12 \]
For the right side:
\[ -3(x + 3) = -3x - 9 \]
So the right side becomes:
\[ -3x - 9 + 21 = -3x + 12 \]
Now the equation simplifies to:
\[ -3x + 12 = -3x + 12 \]
Since both sides of the equation are identical, this means that the equation is true for all values of \(x\). Therefore, the solution to this equation is:
Infinitely many solutions.